Understanding the Dynamics of the Value Chain - Mawhinney, John (Business Expert Press, 2013)
Ebook from IG Library ; In his 1985 book, Competitive Advantage, Michael Porter introduced the concept of the value chain and described it as 'a systematic way of examining all activities a firm performs and how they interact, (necessary) for analyzing the sources of competitive advantage,' and introduced the idea of 'linkages,' which was the real breakthrough in management thinking. Thinking of a firm as a series of horizontal and vertical linkages put the spotlight on the silo mentality within which firms operated and how business schools structured curriculum. The silo mentality caused business students unable to see the firm as a holistic entity, an understanding of how all of its parts fit together to develop competitive advantage. Students graduating with a silo mentality perpetuated the silo mentality in business firms. This book draws together existing knowledge to help facilitate the shift of mind necessary to effectively manage the value chain, and introduces a new conception of the value chain, one that has been copyrighted (2006) and provides a new perspective of the value chain commensurate with the demands of the 21st-century global economy.